2016
DOI: 10.14507/epaa.24.2488
|View full text |Cite
|
Sign up to set email alerts
|

The creation of performance funding in Michigan: Partnership, promotion and points

Abstract: While accountability in higher education has been a topic of debate for decades, in recent years the discussions have shifted to emphasize efficiency and economic measures of success. A prominent example of this accountability movement is the increase in popularity of performance funding policies. One of the most recent states to implement performance funding is Michigan, which began their performance funding policy in 2012. This study explored the creation and implementation of the state of Michigan's perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Twenty-one studies that did not focus on PBF in the United States were excluded (e.g., Frolich et al, 2010; Lang, 2016). Thirty-two studies were excluded that did not focus on the intended or unintended consequences of PBF adoption in any capacity (e.g., Blankenberger & Phillips, 2016; Opoczynski, 2016). Five studies were not included for other reasons not captured in our primary exclusion criteria (e.g., the same study was found to be listed as both a working paper and journal article).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-one studies that did not focus on PBF in the United States were excluded (e.g., Frolich et al, 2010; Lang, 2016). Thirty-two studies were excluded that did not focus on the intended or unintended consequences of PBF adoption in any capacity (e.g., Blankenberger & Phillips, 2016; Opoczynski, 2016). Five studies were not included for other reasons not captured in our primary exclusion criteria (e.g., the same study was found to be listed as both a working paper and journal article).…”
Section: Methodsmentioning
confidence: 99%
“…In light of the general mental hypothesis of the expert advancement of an individual, we have the motivation to state that the way toward distinguishing and further building up an all-encompassing powerful complex of individual, expertly significant characteristics of instructors is changed at each phase of their expert improvement. Financial changes brought about by civilizational changes, for example, the dynamic advancement of creation and the rise of a market economy in global, expect masters to audit and reexamine esteem directions, to understand the significance of skills gained and to create vocation improvement systems (Opoczynski, R. 2016). In this manner, proficient advancement and vocation development of the educator of professional training organization in a market economy infers beating the relating challenges at each phase of expert arrangement and improvement, the consequences of which mirror the level of improvement of individual-individual and expert action parts, joined in the fundamental and foundational segments, honesty.…”
Section: Findings and Discussionmentioning
confidence: 99%